Incidence and risk of falls in patients treated for hematologic malignancies in the Intensive Hematology Unit - Lorca, Luz Alejandra (Rev Lat Am Enfermagem, 2019)
OBJECTIVE: to determine the incidence and rate of risk of falls in adult patients treated for hematologic malignancies in the Intensive Hematology Unit of a reference hospital. METHOD: this is a retrospective observational study. A total of 101 patients were evaluated. The occurrence of falls was obtained from records of the unit and the predictive variables of the Hendrich II model were collected, namely: sex, presence of dizziness or vertigo, mental confusion, elimination problems, depression, use of benzodiazepines, use of anticonvulsants, and the Get up and Go test. RESULTS: two fall events were reported in 101 patients (incidence of 1.98% over a 1.5-year period). Based on the cut-off point 5 of the Hendrich II Model, 30 patients (29.7%) were at risk of fall at the moment of hospital admission, 41 (40.6%) in the middle of the hospitalization period, and 38 (37.6%) at the moment of hospital discharge. CONCLUSIONS: patients treated for hematological malignancies presented low incidence and high risk of falls during hospitalization.